A fast-responsive fluorescent turn-on probe for nitroreductase imaging in living cells. Issue 15 (24th February 2021) - Jia, Chengli; Zhang, Yong; Wang, Yuesong; Ji, Min
Abstract : Probe NTR-NO2 was effectively reduced in the presence of NTR generating a highly fluorescent product. Abstract : Nitroreductase (NTR) may be more active under the environment of hypoxic conditions, which are the distinctive features of the multiphase solid tumor. It is of great significance to effectively detect and monitor NTR in the living cells for the diagnosis of hypoxia in a tumor. Here, we synthesized a novel turn-on fluorescent probe NTR-NO2 based on a fused four-ring quinoxaline skeleton for NTR detection. The highly efficient probe can be easily synthesized. The probe NTR-NO2 showed satisfactory sensitivity and selectivity to NTR. Upon incubation with NTR, NTR-NO2 could successively undergo a nitro reduction reaction and then generate NTR-NH2 along with significant fluorescence enhancement (30 folds). Moreover, the fluorescent dye NTR-NH2 exhibits a large Stokes shift (Δ λ = 111 nm) due to the intramolecular charge transfer (ICT) process. As a result, NTR-NO2 displayed a wide linear range (0–4.5 μg mL −1 ) and low detection limit (LOD = 58 ng mL −1 ) after responding to NTR. In addition, this probe was adopted for the detection of endogenous NTR within hypoxic HeLa cells.